Summary Proceedings of the Twenty-Ninth Annual Meeting of the Board of Governors 1974. - International Monetary Fund. Secretary's Department (Washington, D.C. : International Monetary Fund, 1974)
The speeches made by officials attending the IMF-World Bank Annual Meetings are published in this volume, along with the press communiques issued by the International Monetary and Financial Committee and the Development Committee at the conclusion of the meetings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet